2006
DOI: 10.2478/s11756-006-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites during ontogenetic phase of reproductive structures in Hypericum maculatum

Abstract: Abstract:The distribution patterns of flavonoids hyperoside, isoquercitrin, quercitrin, quercetin, I3,II8-biapigenin and naphtodianthrones hypericin and pseudohypericin were studied in reproductive structures during ontogenetic phase of flowering in Hypericum maculatum CRANTZ. Considerable differences in the content of these secondary metabolites, in the particular flower parts were found. The content of all the metabolites studied is stable during the whole period of flowering in green flower parts (sepals). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…perforatum , the average amounts of hypericin and emodin were found to be 3330 ng/mg (dry weight) and 190 ng/mg (dry weight), which could significantly decrease during a cold acclimation period and remained unchanged after the exposure of plants to dehydration and exogenous abscisic acid treatment [63]. Furthermore, the amount varied within the taxonomical category [64], seasons of harvesting [65], different plant structures [66] and the ontogenetic phases [67]. It is interesting that the emodin content of fungi is higher than that of the hypericin, which is vice versa in plants.…”
Section: Discussionmentioning
confidence: 99%
“…perforatum , the average amounts of hypericin and emodin were found to be 3330 ng/mg (dry weight) and 190 ng/mg (dry weight), which could significantly decrease during a cold acclimation period and remained unchanged after the exposure of plants to dehydration and exogenous abscisic acid treatment [63]. Furthermore, the amount varied within the taxonomical category [64], seasons of harvesting [65], different plant structures [66] and the ontogenetic phases [67]. It is interesting that the emodin content of fungi is higher than that of the hypericin, which is vice versa in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigations on ontogenetic variation of secondary metabolites from different classes have received considerable interest from plant scientists over several decades. In particular, growth and development of the reproductive parts in Hypericum plants is generally followed by acceleration of secondary metabolism resulting in enhanced accumulation of different secondary metabolites such as hypericin, rutin, quercetin, isoquercetin, hyperoside in H. perforatum (Kazlauskas and Bagdonaite 2004; Çirak et al 2007b), H. brasiliense (Abreu et al 2004), H. maculatum (Martonfi et al 2006), total phenolics in H. perforatum, H. pruinatum and H. aviculariifolium (Ayan et al 2006) and hyperforin in H. perforatum (Büter and Büter 2002; Couceiro et al 2006). Our findings in the present study confirmed this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, detecting genotypic variation in the concentration of secondary metabolites is not sufficient to make a substantial conclusion unless other sources of variation are clarified (Walker et al 2001). Because, variation in secondary metabolite concentrations among accessions of H. perforatum may be influenced not only by variance of genotype but also by other factors such as morphologic composition of plant material and the phenological stage in which plants are harvested (Sirvent et al 2002; Martonfi et al 2006). In our previous studies, we documented morphologic, phenologic and population variability of hypericin and several flavonoids (Çirak et al 2007a, b) in H. perforatum growing in Turkey.…”
mentioning
confidence: 99%
“…Phenolics and flavonoids, which are responsible for the biological activities of Hypericum perforatum L., can often be found in the leaves and flowers of a plant (Zobayed et al, 2006) and the disposal model of some flavonoids in plants reproductive complex during the flowering stage was also studied in a related Hypericum species (Mártonfi, 2006). H. perforatum L. is well recognized when it comes to flavonoids content (quercetin and kaempferol at the first place) (Nahrstedt and Butterweck, 2010) which are found in its leaves as glycosides located in special compartments of the cells of epidermis, and which are responsible for UV-protection (Germ, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%